Relevanța analizei erorilor în achiziția articolului în RLS. : Studiu de caz asupra vorbitorilor de armeană - Nicolae Adrian, Hent (Helsinki Romanian Studies Journal, 2024)
This study aims to highlight linguistic and didactic reference points in teaching the article to Armenian language speakers. The acquisition of the article in a foreign language presents a challenge for many learners due to structural differences between languages regarding its use and placement. Additionally, identifying the correct contexts for the use of definite, indefinite, or zero articles complicates the learning process, requiring constant exposure to correct linguistic patterns. Based on empirical data analysis through the error analysis method, the study illustrates, with concrete examples, a series of structural differences and similarities in the use of the article in Romanian and Armenian, drawn from a case study conducted over three years of teaching Romanian at “Valeri Brusov” University in Yerevan, Armenia. The selected corpus consists of 70 written texts, including free compositions and guided essays, produced by students with competence levels ranging from intermediate to advanced. The paper will first summarize the theoretical procedures of error analysis, then focus on identifying, describing, examining, and classifying the main sources of errors in the use of the article by Armenian students. Additionally, the study will explore the impact of negative transfer in the acquisition of the article, considering, as much as possible, how the learners’ proficiency level influences the degree of interference with their native language. The findings demonstrate that, in the case of Armenian speakers, error analysis is an effective, and sometimes essential, tool in identifying recurring mistakes, allowing for the adaptation of teaching strategies to clarify the structural differences between the native language and the target language and to optimize the learning process.